Dewan Editor JAT Vol. 8, No. 2, April 2019 - JAT, Pengelola (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.8, No.2, April 2019, 2019)
Dewan Editor JAT Vol. 8, No. 2, April 2019